2007
DOI: 10.1590/s0100-879x2006005000165
|View full text |Cite
|
Sign up to set email alerts
|

Breathing pattern, thoracoabdominal motion and muscular activity during three breathing exercises

Abstract: The objective of the present study was to evaluate breathing pattern, thoracoabdominal motion and muscular activity during three breathing exercises: diaphragmatic breathing (DB), flow-oriented (Triflo II) incentive spirometry and volume-oriented (Voldyne) incentive spirometry. Seventeen healthy subjects (12 females, 5 males) aged 23 ± 5 years (mean ± SD) were studied. Calibrated respiratory inductive plethysmography was used to measure the following variables during rest (baseline) and breathing exercises: ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 16 publications
3
68
0
11
Order By: Relevance
“…Another study showed that the electromyographic activity of the accessory respiratory muscles is significantly greater during ISFOD than during ISVOD. (10) Our results corroborate the finding that diaphragmatic mobility is greater during ISVOD than during ISFOD.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Another study showed that the electromyographic activity of the accessory respiratory muscles is significantly greater during ISFOD than during ISVOD. (10) Our results corroborate the finding that diaphragmatic mobility is greater during ISVOD than during ISFOD.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have shown differences between the different types of incentive spirometers in terms of respiratory pattern, thoracoabdominal motion, respiratory effort, and accessory muscle recruitment. (8)(9)(10) In the present study, diaphragmatic mobility was measured via ultrasound during the use of incentive spirometers. Our results showed that diaphragmatic mobility was significantly greater during ISVOD and during DB than during ISFOD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy adults, previous studies have reported that VIS induced greater chest wall expansion and abdominal displacement 10,11,19 and lower inspiratory muscle activity 9,11,20 and work of breathing 21,22 than FIS. However, to the best of our knowledge the advice to use incentive spirometry has never been investigated in elderly subjects.…”
Section: Discussionmentioning
confidence: 92%
“…These maneuvers increase transpulmonary pressure and therefore increase chest-wall volume. 9 Parreira et al 10 and Paisani et al 11 showed that VIS promotes a greater chest wall volume with a larger abdominal contribution than does FIS in healthy adult subjects. In addition, Chang et al (2010) 7 and Parreira et al (2005) 10 suggested that the inspiratory flow, rather than the type of incentive spirometry, determines the breathing pattern and the respiratory muscle activation in this population.…”
Section: Introductionmentioning
confidence: 99%